Hydro-chemical assessment of groundwater pollutant and corresponding health risk in the Ganges delta, Indo-Bangladesh region. (1st January 2023) - Biswas, Tanmoy; Pal, Subodh Chandra; Saha, Asish; Ruidas, Dipankar; Islam, Abu Reza Md.Towfiqul; Shit, Manisa
Abstract: Groundwater is the most important source of water among the various water form on the earth's surface. It supports life on the earth and is therefore treated as more significant than surface water. The groundwater of the Ganges delta aquifers has suffered immensely in the last few decades due to various anthropogenic causes apart from natural causes. The high density of population, urbanization, industrialization, and deforestation along the Ganges delta region have been forced to increase the As and F − concentration as human-induced causes apart from natural processes such as high infiltration rate, excessive sedimentation, seawater intrusion, geological formation, etc. The concentration of As and F − in the groundwater aquifers of the Ganges delta increases the vulnerability to various health issues. Extreme exposure to various heavy metals in the groundwater aquifers caused to affect negatively on human health and created different life-losing chronic diseases. Therefore, the present study focused on the assessment of GWQ, evaluation of ecological status, and estimation of probable health risks in the Ganges delta region due to high exposure of As and F − into the groundwater aquifer. The field-based statistical techniques such as degree of contamination (CD), groundwater quality index (GWQI), ecological richness index (ERI), and health risk index (HRI) have been adopted for assessing the As and F − vulnerability including multi-collinearity and correlation matrix. The result illustrates that nearly 50–55% and 60–70% of the Ganges delta region is immensely suffering from poor groundwater quality, ecological diversity, and various health issues in dry and wet seasons respectively in terms of As and F − vulnerability. The USSL and Wilcox diagram confirmed that more than 50% of groundwater aquifers are not suitable for drinking and irrigation. The applied techniques and the outcomes of the current research can be beneficial to the researchers, management authorities, water scientists, and decision-makers in managing the vulnerability of As and F − exposure by adopting sustainable strategies and policies. Graphical abstract: Image 1 Highlights: The variability of GW contamination noticed in the Gangetic delta. About 50–55% and 60–70% area Gangetic delta's GW not suitable for drinking. Extreme As and F − contamination has created serious health issues. Regular monitoring and sustainable policy are recommended.